Phytochemical Investigation of the Stem Bark of Phlogacanthus thyrsiflorus (Roxb.) Nees. - Ilham, S.; Ali, M.S.; Hasan, C.M. (Asian Journal of Chemistry, 2011)
The stem bark of Phlogacanthus thyrsiflorus (Acanthaceae) was subjected to phytochemical investigation. The powdered stem bark was extracted with methanol and then partitioned between chloroform and petroleum ether. Two labdane diterpenes namely 19-hydroxy-labda 8(17), 13-diene-15, 16-olide and ent-labd-8(17), 13-dien-15,16-olide-19-oic acid (pinusolidic acid) and one triterpene betulin were isolated from the chloroform and petroleum ether fraction of the methanolic extract by column chromatography followed by preparative thin layer chromatography. The structure of the compounds were established by high field NMR methods (1H NMR, 13C NMR) as well as by comparison with reported compounds.